Good Governance, International Organization and Policy Transfer: A Case of Indonesian Bureaucratic Reform Policy - Arwanto Arwanto; Wike Anggraini (Magister Ilmu Administrasi Publik, 2022)
In this paper we discuss the connection between the concept of good governance and bureaucratic reform policy. Improving bureaucracy performance can be achieved by implementing good governance. However, another argument posits the notion that bureaucratic reform can lead the way to achieving good governance. Therefore, this paper assesses the relationship between the concept of good governance and bureaucratic reform in Indonesia. The research was based on content analysis technique that analysed the relevancy of good governance criteria and content of policy document, which were supplemented by interviews. Subsequently policy analysis was done using a policy transfer lens. Research findings showed that good governance influences Indonesian bureaucratic reform policy and international organizations have played significant part in influencing the Indonesian government to adopt good governance.